EFL Students’ Perceptions Of Online Learning During The Covid- 19 Pandemic: A Case Study - Dorine Rakaj (International Journal of Educational Management and Innovation, 2022)
The COVID-19 pandemic has drastically changed many things, including education. This study aimed to examine students' perceptions of online learning during the COVID-19 pandemic. The study employed a quantitative approach. Data collection was done by distributing an online questionnaire to 100 selected undergraduate students majoring in English Language and Literature at the University of Prizren, Kosovo. The study's findings indicated that students had negative perceptions of online classes during the COVID- 19 pandemic. Lack of quality, lack of proper interaction and concentration, lack of computer skills were the major problems experienced by undergraduate students at the University of Prizren. Based on the research results, it can be concluded that the respondents of this study were not willing to accept their courses via online mode.